Optimalisasi Pemasaran Digital Koperasi Jasa Gunung Madu Menggunakan Whatsapp Business - magdalena, Betty; Rafiq, Muhammad; Widjayanti , Yoan Budi (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
Gunung Madu Service Cooperative is a cooperative operating in Lampung, precisely in the housing complex II PT GMP, Km 90 Gunung Batin Baru, Terusan Nunyai District, Central Lampung Regency. Gunung Madu Service Cooperative has not yet carried out good marketing activities, both conventionally and digitally. Gunung Madu Service Cooperative already has Whatsapp Business but only focuses on savings and loan services offered to members of Gunung Madu Service Cooperative. However, until now there has been no marketing system on social media or digital marketing strategies such as Whatsapp Business. Meanwhile, in the current digital economy era without digital marketing, there is a loss of opportunity to make it easier for members/customers to provide information related to products or services owned by Gunung Madu Service Cooperative. By using the community service implementation method, this community service is carried out in several systematic stages to ensure the optimization of Gunung Madu Service Cooperative's digital marketing through the use of WhatsApp Business. With the stages of implementation of Problem Identification and Needs Analysis, Whatsapp Business Training and Mentoring, Implementation and Trial of Marketing Strategies, Monitoring and Evaluation, Compiling reports on the results of community service. From the results of the implementation of this program, it is expected that the implementation of WhatsApp Business will significantly help cooperatives in increasing the effectiveness of digital marketing. By utilizing the available business features, cooperatives can reach more customers, speed up responses to questions, and increase the number of transactions